Alternative substrates for growth and production of potted chrysanthemum (cv. Funny) - doi: 10.4025/actasciagron.v33i3.6991 - Terra, Simone Braga (2011)
The identification of alternative substrates that are suitable for the production of potted plants is very important. To this end, we studied the influence of different substrates on the growth and production of potted chrysanthemum (Dendranthema grandiflora Tzvelev cv. Funny). A completely randomized design with four treatments and twelve replicates was used. Each treatment consisted of the following substrates: i) carbonized rice husks; ii) commercial substrate; iii) mixture of vermiculite and carbonized rice husks in a 1:1 proportion; and iv) mixture of vermiculite and washed sand in a 1:1 proportion. Satisfactory results were obtained with alternative substrates, indicating that rice husks can be used as a sole or partial substrate for potted chrysanthemum cultivation, creating a possible new use for this regional agro-industry waste product. Using rice husk as a substrate promoted bud diameters 6% larger than the commercial substrate usually used in Brazil.